Oncology Comparative Effectiveness Research: A Multistakeholder Perspective on Principles for Conduct and Reporting - Ramsey, Scott D. (AlphaMed Press, 2013)
Comparative effectiveness research (CER) can assist patients, clinicians, purchasers, and policy makers in making more informed decisions that will improve cancer care and outcomes. Despite its promise, the factors that distinguish CER from other types of evidence remain mysterious to many oncologists. One concern is whether CER studies will improve decision making in oncology or only add to the massive amount of research information that decision makers must sift through as part of their professional responsibilities. In this report, we highlight several issues that distinguish CER from the most common way evidence is generated for cancer therapy—phase I–III clinical trials. To identify the issues that are most relevant to busy decision makers, we assembled a panel of active professionals with a wide range of roles in cancer care delivery. This panel identified five themes that they considered most important for CER in oncology, as well as fundamental threats to the validity of individual CER studies—threats they termed the “kiss of death” for their applicability to practice. In discussing these concepts, we also touched upon the notion of whether cancer is special among health issues with regard to how evidence is generated and used.